2020
DOI: 10.20956/geocelebes.v4i1.8916
|View full text |Cite
|
Sign up to set email alerts
|

Identifikasi Struktur Bawah Permukaan Di Sekitar Manifestasi Panasbumi Reatoa Kabupaten Maros Menggunakan Survey Geolistrik Resistivitas

Abstract: Penelitian ini bertujuan untuk mengidentifikasi struktur bawah permukaan berupa rekahan pada daerah sekitar manifestasi mata air panas Reatoa di Dusun Realolo, Kabupaten Maros. Beberapa penelitian mengenai panasbumi di Sulawesi Selatan menggunakan geolistrik resistivitas pernah dilakukan untuk mencari zona aquifer hidrothermal di sekitar sumber air panas Panggo di Desa Kaloling, Kabupaten Sinjai. Penelitian ini juga pernah dilakukan dalam eksplorasi mata air panas menggunakan metode geolistrik resisitivitas di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 1 publication
0
0
0
Order By: Relevance
“…In addition, the position of the fracture plane that intersects the layer on the resistivity section is found on the surface of the fracture which is a spring point. According to Syamsuddin et al [6], the resistivity value in a geological structure area will show a higher or lower value than the surrounding rocks.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, the position of the fracture plane that intersects the layer on the resistivity section is found on the surface of the fracture which is a spring point. According to Syamsuddin et al [6], the resistivity value in a geological structure area will show a higher or lower value than the surrounding rocks.…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, research conducted by Anas, A.N. et al [6] explained that fractures cause hot fluids in aquifers to have gaps in the surface and form hot springs. The results of the site survey, it was found that there is the emergence of springs even with a small discharge.…”
Section: Introductionmentioning
confidence: 99%